1986
DOI: 10.1063/1.450302
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure on the Raman spectra of ice VIII and evidence for ice X

Abstract: Raman spectra of H 2 0 and 0 2 0 ice VIII have been measured up to 50 GPa at lOOK. The changes in line positions and intensities of ice VIII and the appearance of a new band above 40 GPa point to the formation of symmetric hydrogen bonds in ice X. A lattice dynamical analysis of the frequency shifts up to 36 GPa suggest a second order phase transition to symmetric hydrogen bonds near 47.5 GPa. However, the observed changes in the lattice modes indicate that this phase transition is already formed by a first or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
78
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(89 citation statements)
references
References 16 publications
11
78
0
Order By: Relevance
“…In connection with the above-mentioned results, we point out that Hirsch and Holzapfel 13 reported the Raman spectra of ice VIII ͑H 2 O and D 2 O͒ up to 50 GPa at 100 K in search of evidence for ice X. They reported that all the bands shift very strongly and the intensities of the 1 B 1g stretching and the Tz A 1g + T x,y E g lattice bands decrease drastically with increasing pressure; also, above 10 GPa, the 1 B 1g stretching and the Tz A 1g + Tx,y E g lattice bands disappear in the background.…”
Section: B Raman Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…In connection with the above-mentioned results, we point out that Hirsch and Holzapfel 13 reported the Raman spectra of ice VIII ͑H 2 O and D 2 O͒ up to 50 GPa at 100 K in search of evidence for ice X. They reported that all the bands shift very strongly and the intensities of the 1 B 1g stretching and the Tz A 1g + T x,y E g lattice bands decrease drastically with increasing pressure; also, above 10 GPa, the 1 B 1g stretching and the Tz A 1g + Tx,y E g lattice bands disappear in the background.…”
Section: B Raman Spectroscopymentioning
confidence: 99%
“…Typically, the OH-stretching vibrational mode of H 2 O ice can be readily followed up to 22 GPa, at which point the 1 A 1g and the 3 E g stretching modes overlap the second-order Raman band of the diamond anvils. 13 The pressure was determined using the R 1 fluorescence technique. 14,15 Ice VIII was prepared by isothermally compressing water at ϳ280 K over 2 GPa so as to cross the liquid-VI-VII phase boundaries in the case of x-ray measurements or compressing ice I h at ϳ220 K over 2 GPa in order to cross the I-II-VI-VIII phase boundaries for the Raman measurements; the cell was then cooled to liquid-nitrogen temperature of 80 K. Ice VIII can be cooled to lower temperatures without phase change.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, experimental and theoretical studies on high pressure ice have shown quantum tunneling of protons in ice VII(47, 51) while higher pressure ices such as ice X exhibit symmetric hydrogen bonds, where the protons are located halfway between two water molecules (51,86,87). The adsorption of water on solid surfaces is an area that has received considerable attention from the surface science community(88-90) and on some 13 surfaces water molecules can be forced into close proximity because of their interaction with the substrate.…”
Section: Tunneling and Proton Delocalization Effectsmentioning
confidence: 99%
“…Advantage of using MH-III for studying the centering is that it is expected to occur at much lower pressure than that of pure ice (ice VII-ice X transition) [10,11,12,13,14,15,16,17,18,19,20], which may make the difficult high-pressure experiments easier. In the following, we calculate the crystal structure and vibrational spectra of MH-III by using the density functional theory, so that we can predict and analyze experimental results.…”
mentioning
confidence: 99%